Caracterização do lodo de esgoto, após desaguamento e secagem térmica, da Estação de Tratamento de Esgoto de Araraquara - Nozela, Weverton Campos [UNESP] (2014)
Disinfection and final disposal of sewage sludge are the more expensive steps in a sewage treatment station. In many Brazilian cities, there is no proper treatment of the sewage. Besides, in a considerable part of the cities which has treatment system of sewage, the sludge generated in the process is not treated at all. Araraquara, a city in São Paulo's interior, nationally stands out for possessing a modern system of draining and thermal drying sewage sludge. The final disposal of its sludge, after being cleaned, is mostly by landfill. However, the inappropriate of the sewage sludge could compromise the environmental and sanitary benefits expected from the sewage treatment system. The possible presence of pollutants in the sludge, such as potentially toxic metals, pathogens and persistent organic compounds are factors that may cause negative environmental impacts, which could make the application of this waste not viable for certain purposes. Therefore, studies are necessary in order to determine if there are short and long-term environmental risks in the use of this sludge. In this research characterized the sludge produced by the Sewage Treatment Station of Araraquara (STSA), after the processes of draining and thermal drying, and may infer that it is a heterogeneous matrix presenting 48,7% organic matter in its composition that provides potential hydrogen gas (H2) generation and calorific power superior to 12 MJkg-1. STSA sludge also has low concentration of the metals Cd, Cu, Cr, Fe, Mn, Ni and Zn, according to the Brazilian legislation currently in force, which rules the agricultural use of sludge. The results obtained from this study indicate that appropriate practices of management and treatment of those residues are possible, as well as its reuse, especially as a fertilizer. or as an energetic source. Added to this, the energy potential for the sludge and the presence of bacteria consortia...